THE VALUE OF PAINTING IN THE ABSTRACT STYLE OF COLORING - Mirabdullayev Azizbek Rasuljon Ogli (Western European Studies, 2024)
In this article, it is written that one of the types of art discovered on the basis of abstract painting and the harmony of consciousness and thinking is the connection of color and music. In particular, it is mentioned that the monad of color and music is related to the work of the abstract artist Kandinsky. And researchers have been thinking about the connection between color, emotion and music.
Keywords: Abstraction; consciousness; color image; Kandinsky